If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4y=3(y-7)
We move all terms to the left:
4y-(3(y-7))=0
We calculate terms in parentheses: -(3(y-7)), so:We get rid of parentheses
3(y-7)
We multiply parentheses
3y-21
Back to the equation:
-(3y-21)
4y-3y+21=0
We add all the numbers together, and all the variables
y+21=0
We move all terms containing y to the left, all other terms to the right
y=-21
| 4y=3.y | | 4y=3.y | | 4y=3.y | | v/9+14=20 | | 3n+(-5)=22 | | -5(2x-1)-(4-3x)=2(4-3x)-10 | | -5(2x-1)-(4-3x)=2(4-3x)-10 | | 0.30x+0.05=0.05(x+15) | | 0.30x+0.05=0.05(x+15) | | -5(2x-1)-(4-3x)=2(4-3x)-10 | | -5(2x-1)-(4-3x)=2(4-3x)-10 | | 2/3x+1/3=20 | | 2/3x+1/3=20 | | 2/3x+1/3=20 | | 4.4m=1.2=9.8 | | 4.4m=1.2=9.8 | | 5(2x−3)−6x=21(4x−10) | | x+8/3=21 | | 1.3Xx=13 | | 1.3Xx=13 | | 3−0.5(4x+8)+5x=9−2x | | 3u=6+5u | | 3u=6+5u | | 3u=6+5u | | 3u=6+5u | | 3−0.5(4x+8)+5x=9−2x | | 3−0.5(4x+8)+5x=9−2x | | 11x+2-10=37-4x | | 11x+2-10=37-4x | | 2x+15=4x−45 | | -15=5(2b-17) | | 6(x+1)-3(x+2)=60 |